Sainfoin varieties adapted to the conditions of the south of Russia - S. A. Ignatiev; T. V. Gryazeva; N. G. Ignatieva (Зерновое хозяйство России, 2018)
The article considers the study results of the sainfoin variety ‘Sudar’, introduced into the State List of Breeding Achievements and approved to use in the North-Caucasus region and the sainfoin variety ‘Shuravi’, sent to the State Variety Testing in the same year. The productivity of both new sainfoin varieties largely depended on the conditions in the period of sowing. During the first cycle of sowing the variety ‘Sudar’ produced 27.4 t/ha of green chop, the variety ‘Shuravi’ produced 29.4 t/ha, that exceeded the standard on 7.8% and 15.7% respectively. On average during two cycles of sowing the standard variety ‘Zernogradsky 2’ produced 27.9 t/ha of green chop, the variety ‘Sudar’ 30.8 t/ha and ‘Shuravi’ produced 31.5 t/ha. On average during two cycles of sowing the variety ‘Sudar’ produced 7.68 t/ha of dry matter and the variety ‘Shuravi’ produced 8.32 t/ha that is on 14% and 23% higher than of the standard variety. The variety ‘Sudar’’s productivity of seeds was 0.75 t/ha, that is on 27% higher than of the standard variety. The variety ‘Shuravi’’s productivity of seeds was 0.80 t/ha, that is on 36% higher than of the standard variety. The comparison of biochemical composition of vegetative mass of sainfoin varieties showed that the largest significant differences among new sainfoin varieties and the standard variety occurred in the content of protein and ash. The study of forage value of the sainfoin varieties established that these varieties exceed the standard variety in the amount of fodder units per hectare, amount of raw and digestible protein and ash. The variety ‘Shuravi’ surpasses the variety ‘Sudar’ in all these traits and in the amount of gross exchangeable energy as well. The leaching of nitrogen, phosphorus and potassium differed through the cycles among the varieties. The standard variety ‘Zernogradsky 2’ leached 174.5-212.1 kg/ha of nitrogen, 39.5-47.7 kg/ha of phosphorus and 100.3-123.3 kg/ha of potassium. The varieties ‘Sudar’ and ‘Shuravi’ exceed the standard on 15-30% in nitrogen leaching, on 14-27% in phosphorus leaching and on 15-28% in potassium leaching. The variety ‘Shuravi’ showed the largest leaching of the elements. The use of vegetative mass of sainfoin varieties as green fertilizer mixed with a ton of dry matter can supply the soil with 28.7-32.9 g/ha of nitrogen, 6.5-7.2 kg/ha of phosphorus and 16.5-18.7 kg/ha of potassium.